Kinerja Aparat Kepolisian Dalam Penegakkan Hukum Pertambangan Tanpa Izin Pada Wilayah Hukum Kantor Kepolisian Resor Morowali - Irma, Ade; Ahdi, Moh (Sekolah Tinggi Ilmu Administrasi (STIA) Pembangunan Palu, 2025)
Thepurpose of this research is to find out how the performance of the police apparatus in enforcing the law on illegal mining activities in the jurisdiction of the Morowali Resort Police Office. the type of research used is qualitative descriptive. the location of the research is the Morowali Police. The informants are the Head of Criminal Investigation, KBO of Criminal Investigation, members of the Criminal Investigation Unit and the mining community which are taken by Purpossive Sampling Namely, a total of 5 people are involved in the technique of determining the sample based on selecting people who are considered to know the problem. Data collection techniques through direct interview observation and documentation as well as data analysis using Data Recording, Data Reduction, Data Display, Data Verification and Conclusion. The results of the research on the performance of the police in the effectiveness of law enforcement against illegal mining in the jurisdiction of the Morowali Police, it can be concluded that the performance of the police has two aspects that have been running well, namely the indicator The quality of the work of the police in dealing with illegal mining in Morowali is relatively good, the indicator of the quantity of work of the police also shows good results, However, they still face obstacles in the implementation of tasks that are still not good and are considered less than optimal.